2011
DOI: 10.1111/j.1365-2591.2011.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic-periodontal management of two rooted maxillary lateral incisor associated with complex radicular lingual groove by using spiral computed tomography as a diagnostic aid: a case report

Abstract: The key to achieving favourable results in this particular type of developmental anomaly is accurate diagnosis and treatment planning. The health of the periapical osseous tissues appears to be the provital factor for tooth retention. A favourable outcome can only be achieved with a comprehensive treatment approach that effectively manages all local factors that are contributing to the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…, Gandhi et al . ). The application of NaOCl at >3% concentration and ultrasonic irrigation may be beneficial (Low & Chan , Schwartz et al .…”
Section: Literature Search Methodologymentioning
confidence: 97%
See 2 more Smart Citations
“…, Gandhi et al . ). The application of NaOCl at >3% concentration and ultrasonic irrigation may be beneficial (Low & Chan , Schwartz et al .…”
Section: Literature Search Methodologymentioning
confidence: 97%
“…The root canal system of double-rooted incisors having a palato-gingival groove shows considerable variations (Table S4). Some authors reported the successful detection of two root canals in the main and accessory roots (Peikoff et al 1985, Greenfeld & Cambruzzi 1986, Gu 2011, whereas others were unable to find a patent root canal space in the accessory root even with 3D radiographic imaging (Sch€ afer et al 2000, Yavuz et al 2008, Gandhi et al 2011.…”
Section: Palato-gingival Groovementioning
confidence: 99%
See 1 more Smart Citation
“…[16] As a result of this breach in the epithelial attachment, the progression of bacterial products through dentinal tubules could secondarily compromise the pulp tissue, causing a primary periodontic/secondary endodontic lesion which necessitated both pulpal and periodontal therapy. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Dental computerized tomography software may be superior to panoramic or intra-oral radiographs [3]. Pulp testing, culture and sensitivity testing of the fluid which is drained i.e., saliva, pus, or cystic fluid, should also be performed, to rule out fungal and syphilitic infections [4].…”
Section: Discussionmentioning
confidence: 99%